Expectant Management Leading to Successful Vaginal Delivery following Intrauterine Fetal Death in a Woman with an Incarcerated Uterus - Masafumi Yamamoto; Mio Takami; Ryosuke Shindo; Michi Kasai; Shigeru Aoki (Case Reports in Obstetrics and Gynecology)
Expectant management leads to successful vaginal delivery following intrauterine fetal death in a woman with an incarcerated uterus. Management of intrauterine fetal death in the second or third trimester of pregnancy in women with an incarcerated uterus is challenging. We report a case of successful vaginal delivery following intrauterine fetal death by expectant management in a woman with an incarcerated uterus. In cases of intrauterine fetal death in women with an incarcerated uterus, vaginal delivery may be possible if the incarceration is successfully reduced. If the reduction is impossible, expectant management can reduce uterine retroversion, thereby leading to spontaneous reduction of the incarcerated uterus. Thereafter, vaginal delivery may be possible.